Detection of Vaccine-Induced Antibodies to Ebola Virus in Oral Fluid. (22nd February 2016) - Lambe, Teresa; Rampling, Tommy; Samuel, Dhan; Bowyer, Georgina; Ewer, Katie J.; Venkatraman, Navin; Edmans, Matthew; Dicks, Steve; Hill, Adrian V. S.; Tedder, Richard S.; Gilbert, Sarah C.
Abstract: Blood sampling to assess production of antigen-specific antibodies after immunization is commonly performed, but it presents logistical difficulties for trials carried out during an infectious disease outbreak. In this study, we show that antibodies may be reliably detected in oral fluid collected in a minimally invasive manner without use of sharps. Clinical Trials Registration.  NCT02240875.